PENINGKATAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG HURUF KONSONAN (P, Q, R, X, F) MELALUI MODEL EXPLICIT INSTRUCTION PADA SISWA KELAS II SDN SEMANAN 05 - Erwandi, Asilah Muthi'ah; Sakmal, Juhana; Syarif Sumantri, Mohamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the writing skills of second-grade students at SDN Semanan 05 Jakarta Barat by applying the Explicit Instruction learning model to write connected upright consonants (p, q, r, x, f). The subjects of this research are 32 students. The method used is Classroom Action Research (CAR) conducted in two cycles, including planning, implementation, observation, and reflection. Data collection techniques involved observation, writing skills tests, and interviews, which were analyzed descriptively and quantitatively. The research results show an improvement in each cycle. In cycle I, the average student score was 72 with a learning completeness of 68.75%. In cycle II, the average score increased to 79 with a learning completeness of 90.63%. Additionally, teacher and student activity in cycle II reached 91.67% and 83.33%, respectively. Based on these results, the implementation of the Explicit Instruction model has proven to enhance students' cursive writing skills. This model can be used as an effective alternative for learning in elementary schools.